2010
DOI: 10.1182/asheducation-2010.1.210
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Anticoagulation: Applying the Guidelines and Beyond

Abstract: Despite an improved understanding of the risk factors underlying venous thromboembolism (VTE), extensive clinical investigation, and detailed clinical guidelines, the decision to extend anticoagulation indefinitely for an individual patient with VTE is often problematic. Patients with VTE in association with major surgery, trauma, immobilization, or pregnancy are at relatively low risk of recurrence and generally do not require more than 3 to 6 months of anticoagulant therapy. For patients with a first unprovo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Determining the period for assessing the expected results, i.e., the performance of the patient when participating in an educational intervention focused on self-care with the OAT will be linked to the reality of each health service. [28][29][30] As regards our reality, it was suggested that this review was conducted two months after the participant's discharge.…”
Section: Expected Results (Performance Phase)mentioning
confidence: 99%
“…Determining the period for assessing the expected results, i.e., the performance of the patient when participating in an educational intervention focused on self-care with the OAT will be linked to the reality of each health service. [28][29][30] As regards our reality, it was suggested that this review was conducted two months after the participant's discharge.…”
Section: Expected Results (Performance Phase)mentioning
confidence: 99%
“…persisting risk factors and previous venous thromboembolism); and (iii) the consequences of recurrence or progression (extensive bowel involvement and short bowel syndrome). 274 Patients with the new risk factors for MVT, such as JAK2 mutation with or without myeloproliferative disorders, should be considered for indefinite treatment, given the persistent nature of their risk factors. The advantage of prolonged anticoagulation should be balanced with the risk of major bleeding, including recent major haemorrhage, uncontrolled hypertension, serum creatinine >1.2 mg/dL, anaemia, or age >75.…”
Section: Follow-upmentioning
confidence: 99%
“…The advantage of prolonged anticoagulation should be balanced with the risk of major bleeding, including recent major haemorrhage, uncontrolled hypertension, serum creatinine >1.2 mg/dL, anaemia, or age >75. 274 Other studies have suggested that the optimal duration of anticoagulant treatment should also take into consideration the recanalisation rate of the mesenteric veins, as this may greatly affect mesenteric venous haemodynamics and, consequently, the risk of recurrence. DUS at 1 and 3 and 6 months after an endovascular procedure may allow examination of the portal system and shunting function after TIPS.…”
Section: Follow-upmentioning
confidence: 99%
“…Despite these associations, measurement of clotting factor levels is not routinely included in a thrombophilia evaluation (9). Clotting factor assays are not standardized for thrombophilia testing and threshold values for identifying high-risk individuals vary considerably among the different populations studied (9).…”
Section: Elevated Clotting Factor Levelsmentioning
confidence: 99%